Penggunaan Vermikompos dalam meningkatkan mutu inokulum fungi mikoriza arbuskula - Asrianti Arif; Husna Faat; Mahfudz Mahfudz (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2009)
Arbuscular mycorrhyza fungi (AMF) constitutes one of biological agent which is able to enhance the growth and productivity of plant. AMF reproduction has been frequenly done as well as inoculum formulation improvement. It is done by adding other subtances like organic fertilizer which is aimed at speeding up plant growth response prior to associating with AMF and increasing more growth after associating with AMF. Thus, This research is aimed at studying the response of AMF selected types G.etunicatum and Glomus sp. Toward vermicompost and test vermicompost addition in increasing AMF inoculum quality. The research is factorial experiment with RAL using two treatment factors. First factor is AMF inoculum factor and the second factor is medium formulation. The research revealed that G.etunicatum is more tolerant on vermicompost addition compared to Glomus sp. (indegenous), the use of vermicompost, G.etunicatum type with 30% vermicompost namely 0,12 x 104 propagul and Glomus sp. Type with 40% vermicompost is 0,19 x 104. Vermicompost residual as early nutrient supply for crop